2021
DOI: 10.21203/rs.3.rs-1069506/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrical Control of Quantum Emitters in a Van der Waals Heterostructure

Abstract: Controlling and manipulating individual quantum systems in solids underpins the growing interest in development of scalable quantum technologies1, 2. Recently, hexagonal boron nitride (hBN) has garnered significant attention in quantum photonic applications due to its ability to host optically stable quantum emitters3-7. However, the large band gap of hBN and the lack of efficient doping inhibits electrical triggering and limits opportunities to study electrical control of emitters. Here, we show an approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It is worth noting that, in recent studies on the effect of electrostatic field on h-BN emitters, , it has been observed that the emitter charge state can be modulated because of electrostatic doping, such that the emitter can switch between optically dark and bright states. However, we do not observe such an effect here.…”
mentioning
confidence: 99%
“…It is worth noting that, in recent studies on the effect of electrostatic field on h-BN emitters, , it has been observed that the emitter charge state can be modulated because of electrostatic doping, such that the emitter can switch between optically dark and bright states. However, we do not observe such an effect here.…”
mentioning
confidence: 99%
“…Recently, White et al designed a heterostructure based on hBN multilayers, hosting SPEs and graphene. 7 By applying a transversal voltage, they successfully toggled specific SPEs on and off, demonstrating precise control over the filling of their electronic levels.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In these systems, the individual layers mutually influence each other, often bringing new functionality to the entire structure. Recently, White et al designed a heterostructure based on hBN multilayers, hosting SPEs and graphene . By applying a transversal voltage, they successfully toggled specific SPEs on and off, demonstrating precise control over the filling of their electronic levels.…”
Section: Introductionmentioning
confidence: 99%
“…Vertically stacked 2D materials can generate periodic moiré superlattices due to lattice mismatches or twist angles 7 . The moiré potential in the moiré superlattice dominates the kinetic energy within the mini-Brillouin zone, which changes the electronic band structure in the heterojunction [8][9][10] , and induces strongly correlated quantum phenomena: including strongly correlated insulators [11][12][13][14] , superconductivity 15 , moiré excitons [16][17][18] , moiré phonons 19,20 , magnetism 21 . Moiré superlattices in twisted two-dimensional (2D) material heterojunctions offer opportunities for the development of many-body physics 22,23 , which will help to drive the development of novel quantum devices 24 .…”
Section: Introductionmentioning
confidence: 99%